Urgensi Pelaksanaan Pengawasan Kemetrologian Legal Guna Mewujudkan Kabupaten Bangka Selatan Daerah Tertib Ukur - Alfarisa, Suhufa (Universitas 17 Agustus 1945 Surabaya, 2021)
Based on the 2014 Regional Autonomy Law, the implementation of legal metrology in the form of calibration, re-calibration and supervision is now the authority of the district/city. This study is expected to provide information related to legal metrology in general and particularly the importance of implementing metrological supervision in the regions. This research was conducted with a qualitative approach with the method of literature review and case studies in Bangka Selatan Regency. The low number of Measuring, Dosing, Weighing Equipment and Their Equipment (UTTP) and Packaged Goods (BDKT) in accordance with the provisions of the legislation is the main factor that causes the importance of this metrological supervision activity to be carried out, in addition to the low level of public understanding or knowledge regarding metrology. legal. In the end, effective metrological monitoring activities can help create an Orderly Measurement Area that is able to provide protection to consumers, especially in trade transactions.